Rancang Bangun Sistem Keamanan Kolam Ikan Berbasis IoT dan Sensor Gerak Passive Infra-Red (PIR) - Deri, Rahmi Rismayani; Faisal, Restu; Permana, Muhammad Rafif; Madani, Adnan; Samsudin, Muhammad (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Theft and disturbance of wild animals in fish ponds is still a serious challenge that has not been optimally handled by conventional security systems. This research designed an IoT-based security system using Arduino Uno R3, PIR sensors, buzzers, and LEDs as an effective and economical solution. The method used is research and development (R&D) with the stages of design, implementation, and testing. The results of the functional test showed that the PIR sensor detected movement up to 7 meters with a response of 0.2 seconds, while the notification system worked effectively. Field simulations recorded 87% accuracy and the system remained stable in the operational conditions of the pool. User surveys resulted in an average score of 4.5 out of 5. The system offers novelty in simple yet reliable integration for an open environment. Implicitly, this technology can significantly improve pond safety and is easily adopted by small-scale fish farmers. Keywords: Arduino, PIR sensor, Pool security